Repeatability of Peripapillary OCT Angiography in Neurodegenerative Disease - Justin P. Ma, BS; Cason B. Robbins, MD; Sandra S. Stinnett, DrPH; Kim G. Johnson, MD; Burton L. Scott, MD, PhD; Dilraj S. Grewal, MD; Sharon Fekrat, MD, FASRS (Ophthalmology Science, 2021)
Purpose: To assess the repeatability of peripapillary OCT angiography (OCTA) in those with Alzheimer disease (AD), mild cognitive impairment (MCI), Parkinson disease (PD), or normal cognition. Design: Cross-sectional. Participants: Patients with a clinical diagnosis of AD, MCI, PD, or normal cognition were imaged. Those with glaucoma, diabetes mellitus, vitreoretinal pathology, and poor-quality images were excluded. Methods: Each eligible eye of each participant underwent 2 OCTA 4.5 × 4.5-mm peripapillary scans in a single session using a Zeiss Cirrus HD-OCT 5000 with AngioPlex (Carl Zeiss Meditec). The Zeiss software (v11.0.0.29946) quantified measures of perfusion in the radial peripapillary capillary (RPC) plexus in 4 sectors (superior, nasal, inferior, temporal). The average of these sectors was calculated and reported. Main Outcome Measures: Radial peripapillary capillary plexus perfusion was quantified using 2 parameters: capillary perfusion density (CPD) and capillary flux index (CFI). Intraclass correlation coefficients (ICCs) were used to quantify repeatability. For subjects who had both eyes included, the average values of each scan pair were used to assess interocular symmetry of CPD and CFI. Results: Of 374 eyes, 46 were from participants who had AD, 85 were from participants who had MCI, 87 were from participants who had PD, and 156 were from participants who had normal cognition. Capillary perfusion density ICC in AD = 0.88 (95% confidence interval [CI], 0.79–0.93), MCI = 0.95 (0.92–0.96), PD = 0.91 (0.87–0.94), and controls = 0.90 (0.87–0.93). Capillary flux index ICC in AD = 0.82 (0.70–0.90), MCI = 0.87 (0.80–0.91), PD = 0.91 (0.87–0.94) and controls = 0.85 (0.79–0.89). There were no significant differences in interocular variation in average CPD and CFI in AD, MCI, or PD (all P > 0.05). Isolated interocular sectoral CPD differences were noted in AD (nasal, P = 0.049; temporal, P = 0.024), PD (nasal, P = 0.036), and controls (nasal, P = 0.016). Interocular differences in CFI in the superior sector in MCI (P = 0.028) and in average CFI for controls (P = 0.035) were observed. Conclusions: Peripapillary OCTA repeatability in AD, MCI, and PD is good-excellent and similar to those with normal cognition. Insignificant interocular asymmetry in peripapillary OCTA suggests neurodegeneration may proceed uniformly; future studies may reveal the appropriateness of single-eye imaging.